(untitled) (Palíndromo, 2021)
This article focuses on the Nymph present in the works of plastic artist Adriana Varejão (1964-). Born in Rio de Janeiro, Varejão’s imagery is a highlight in the contemporary artistic circuit. The images are analyzed through theorical questions articulated with the Nymph, raised by art historian Aby Warburg works, and incorporated and revisited by the works of Georges Didi-Huberman in art history. The nymphs in Varejão were singled out from three of the images present in the series Saunas e Banhos - entangled in the tiles, beloved object by the artist - through the similarities with images produced in other historical periods, also problematized as nymphs.